Poor Fetal Heart Rate Variability in a Pregnant Woman with Acute Appendicitis - Chih-Cheng Huang; Tien-Hui Chen; Kuo-Cherng Lin (Elsevier, 2005)
Objective: Fetal heart rate (FHR) variability indicates autonomic nervous system response. Absence of variability may be due to various causes, including fetal metabolic acidosis, neurologic abnormality, marked prematurity, cardiac arrhythmia, effects of drugs, fetal sleep or inactivity. We present the case of a pregnant woman with acute appendicitis whose fetus demonstrated poor variability in heart rate, and we explore the possible reasons that caused poor variability in FHR in this patient. Case Report: A pregnant woman at 40+1 weeks of gestation was admitted because of acute right lateral subcostal tenderness and rebounding pain. Under the impression of acute appendicitis, emergency appendectomy was arranged. Epidural combined with general anesthesia were offered to the patient. Absent variability of FHR on fetal monitoring was noted immediately after laparotomy, and did not reappear until 5 hours after the operation. Emergency cesarean section with spinal anesthesia was arranged due to prolonged active phase in cervical dilatation. The fetus was born with Apgar scores of 6 and 8 at 1 and 5 minutes, respectively. Abdominal sepsis due to acute appendicitis that subsequently caused chorioamnionitis and fetal infection was the most probable reason for the poor FHR variability. Conclusion: When sources of infection are eradicated from a pregnant patient, whether by surgical or medical methods, FHR variability will gradually return. Seldom is cesarean section indicated at the time of appendectomy. We suggest that the choice of delivery should depend on the obstetric indications, and not on the event of acute appendicitis.